UNDERSTANDING INTENTION TO USE PAYLATER: ROLES OF FINANCIAL LITERACY, RISK, AND TRUST - Dewi, Anisa Kurnia; Mardi; Indriani, Susi (Jurnal Pendidikan Ekonomi, Perkantoran, dan Akuntansi, 2025)
This study was conducted to explore how financial literacy and risk perception influence the intention to use PayLater, with trust examined as a moderating factor. A quantitative approach was adopted, and data were collected from 252 students of the Faculty of Economics and Business, Universitas Negeri Jakarta, class of 2021. Using SPSS version 26, multiple linear regression and moderated regression analysis (MRA) were used to evaluate the data. The findings showed that while risk perception significantly influences intention negatively, financial literacy significantly influences intention positively. Furthermore, it was demonstrated that trust moderated these associations by enhancing the beneficial effects of financial literacy and diminishing the detrimental effects of risk perception. These findings emphasize the need to promote financial awareness and strengthen user trust to support the responsible use of PayLater among students.